Research on the Incentive Mechanism and Implementation Path of Resource Recycling from the Perspective of a Sustainable Economy - Sun, Yishu (International Journal of Global Economics and Management, 2024)
With the advancement of the global sustainable development agenda, recycling resources has become an important strategy to promote sustainable economic development. This study examines the significance of resource recycling in fostering environmental conservation, conserving energy, and enhancing resource efficiency through a comprehensive analysis of sustainable economic theory. This paper thoroughly analyzes and examines the incentive mechanism and execution strategies for resource recycling, encompassing policy incentives, market dynamics, social responsibility, and technological innovation. Through comparative case analysis and theoretical construction, the paper aims to provide feasible strategies and operational suggestions for enterprises and policymakers to realize resource recycling, thereby promoting the green transformation of the economy. The research findings demonstrate that effective policy incentives such as tax reduction, subsidies, and environmental regulations are the core driving forces for promoting resource recycling. Additionally, innovative market mechanisms such as green labels and developing circular economy market platforms can enhance enterprises' engagement in resource recycling. The achievement of corporate social responsibility and the enhancement of consumers' awareness regarding environmental protection positively influence resource recycling. In conclusion, technological innovation and improvement are essential for efficient resource circulation. Intelligent and digital technology has greatly improved the recovery rate and resource reuse efficiency.